ANALISIS PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP PENINGKATAN PENDAPATAN MUSTAHIK DI KABUPATEN SRAGEN - Tri Yulianingsih; Arif Pujiyono (Diponegoro Journal of Islamic Economics and Business, 2025)
Poverty remains a major challenge in Sragen Regency, with a higher rate than the national average. Productive zakat offers a solution by serving not only as social aid but also as a tool for economic empowerment. When utilized effectively, it can enhance skills, create business opportunities, and promote financial independence among mustahik. This study analyzes the impact of productive zakat utilization, workforce training, and monitoring on mustahik income using a quantitative approach with multiple linear regression. Primary data was collected from 193 mustahik receiving productive zakat from BAZNAS Sragen in 2023. The results show that all three variables positively and significantly affect mustahik income. The t-test results for productive zakat (t = 2.953), training (t = 3.428), and monitoring (t = 4.322) exceed the t-table value (1.972) with Sig. < 0.05. The F-test confirms the model’s significance (F = 41.421, Sig. = 0.000), with R² = 39.7%, indicating strong explanatory power. In conclusion, optimizing zakat utilization, effective training, and monitoring are crucial for increasing mustahik income. Future research should apply Policy Evaluation Tool (PET) Analysis for better program assessment.